THE INFLUENCE OF SOCIAL MEDIA MARKETING FACTORS ON CONSUMER PURCHASE DECISION - Pratama, Ikhwan; Firdi willy; Kamila Luna Annabil; Alisa Zahra Putri (Lentera Jurnal Pengabdian Masyarakat, 2026)
The impact of social media marketing elements on customer purchasing decisions is investigated in this study. As independent factors, the study focuses on influencer credibility, brand perception, promotion exposure, and trust. Multiple linear regression was used to evaluate the quantitative data that was gathered from 218 respondents via online surveys. The results demonstrate that while influencer credibility has no discernible impact on customer purchasing behavior, promotion exposure, trust, and brand perception have a substantial beneficial impact on purchase decisions. Purchase decisions are most strongly influenced by promotion exposure out of all the variables. According to the study’s findings, constant promotion, customer trust, and favorable brand perception should be given top priority in social media marketing tactics in order to promote consumer behavior.